Parental perceptions of dental health in children with neurological disorders: Cross-sectional tertiary care center assessment - Anas S Alyazidi; Sara Y Muthaffar; Arwa Y Muthaffar; Osama Y Muthaffar; Mahmoud A Gaddoury (Wolters Kluwer Medknow Publications, 2022)
Introduction: Neurological disorders present in different age groups. In children, the spectrum of neurological diseases is multifactorial and varies between motor delay, speech delay, cognitive delay, and global developmental delay. Dental caries constitutes a public health problem that impacts approximately 80% of children nationwide. Aims: This study aims to evaluate the magnitude of dental problems in children with neurological disorders. Materials and Methods: An epidemiological investigation using a cross-sectional design was conducted. A total number of 2451 electronic surveys were sent to parents of children attending the pediatric neurology clinic. Children who attended the clinic from January 2017 to January 1, 2021, were included. Six hundred and seventy-five parents (28%) answered the survey. Statistical Analysis Used: For statistical analysis, IBM SPSS Statistics for Windows (Version 21.0; IBM Corp., Armonk, NY, USA) software was used. Categorical variables were presented using numbers, associated frequencies, and percentages (%). Categorical variables were correlated using the Chi-square test. Results and Discussion: A total number of 2451 surveys were distributed. The response rate was 28%. A total of 675 patients were labeled eligible. Patients' gender characteristics were as follows: 389 (58%) were male while 286 (42%) were female. Patients were distributed into two age groups, a group aged <7 years old and 7-14 years old. Conclusions: Neurological disorders proved to be a burden on patients with dental caries and their families. Socioeconomic status was an important aspect in the families' ability to manage dental caries. Patients with complicated seizures and require multiple drugs were more prone to worse states of oral hygiene. Multidisciplinary care that combines dentists and medical physicians is required.